Tarak-urban the Tacloban City socio-culture hub - Barcena, Junelle B.
Years after the onslaught of Typhoon Haiyan in 2013, Tacloban City and its neighbors have been rebuilding with the help and generous contributions of organizations worldwide. Despite this, the city is facing an identity crisis, now being branded as the most easily conjured image of the devastation brought about by the storm. The crisis is starting to ingrain itself in the minds of the residents, they themselves embracing this identity as typhoon survivors, and though this is not necessarily wrong, Tacloban is so much more than just a resilient city. There arises the need to provide the people with a venue to channel their positive actions and take advantage of the empathy people still feel for each other. The project is a socio-culture hub geared at enhancing the daily and seasonal social activities of Taclobanons. It is located on the site of RTR Plaza, easily accessible from any point in the city and even beyond. Spaces are designed to be multi-purpose and multi-use in order to adapt to changing needs and concerns, appeal to a wider range of audiences, and overall function to its optimal capacity. There is also an abundance of activities to do to help foster positive social relationships among users. The project is geared toward a vision of a happier, healthier, culture-oriented Tacloban where people have a strong sense of community.